The improved modified extended tanh-function method to develop the exact travelling wave solutions of a family of 3D fractional WBBM equations - Mamun, Abdulla – Al –; Ananna, Samsun Nahar; Gharami, Partha Protim; An, Tianqing; Asaduzzaman, Md (Results in physics, 2022)
•The highlights of the paper entitled “The improved modified extended tanh-function method to develop the exact travelling wave solutions of a family of 3D fractional WBBM equations” Fractional order partial differential equationshave been considered by many scientists because of their important applications in nonlinear science and physics. It has great importunacy to obtain exact solutions of the nonlinear fractional order partial differential equationsto seek the wave phenomena that they describe.•In this paper, we dealt with exact solutions of nonlinear fractional partial differential equations.•We hope that our results are going to be useful for applied sciences in forward studies. The improved modified extended tanh-function (imETF) method is used to develop exact traveling wave solutions of a family of 3D fractional Wazwaz-Benjamin-Bona-Mahony (WBBM) equations. Bright solitons, dark solitons, bright-dark solitons, single solitons, and multiple solitons are obtained by using the imETF method. Also, periodic solutions, singular periodic solutions, hyperbolic function solutions, rational function solutions, trigonometric function solutions, and exponential function solutions are reported. Through companionable wave transformation, the governing equations are simplified to conventional ordinary differential equations. The alternative solution relates to the earlier phase. The anticipated solution's power coefficients are compared to create a system of algebraic equations (SAE). The links between parameters and coefficients that are required to create solutions are provided by a resilient coefficients scheme. For various parameter combinations, certain solutions are modeled.